STRATEGI PEMASARAN DIGITAL IDWEBHOST MELALUI PLATFORM INSTAGRAM - Setiawan, Iwan (Istek Widuri Jakarta, 2025)
This research aims to explore IDwebhost's digital marketing strategy through the Instagram platform, using a qualitative approach and discourse analysis. As a leading hosting service provider in Indonesia, IDwebhost has utilized Instagram as one of its main platforms to interact with its audience and promote its products. This research focuses on how IDwebhost builds its brand image and attracts the audience's attention through creative content published on the Instagram platform. Through discourse analysis, this research explores how the messages conveyed in advertisements and posts on Instagram shape meaning and influence the audience's perception of the IDwebhost brand. Data was collected through purposive selection of IDwebhost's Instagram posts and analyzed with a focus on the textual, visual, and narrative elements used in the content. The findings show that IDwebhost uses various strategies, such as attractive visuals, clear calls-to-action, and narratives that build trust, to create an emotional connection with the audience. This research also reveals how these elements play a role in shaping a more inclusive and accessible discourse of the IDwebhost brand, especially for potential customers who are new to hosting services and for customers who have previously enjoyed services from IDwebhost. Based on these findings, this research suggests that other digital companies can adopt a similar approach in building trust and engagement on social media platforms.